2021
DOI: 10.3390/ijerph18168870
|View full text |Cite
|
Sign up to set email alerts
|

The Significance of Occupants’ Interaction with Their Environment on Reducing Cooling Loads and Dermatological Distresses in East Mediterranean Climates

Abstract: Global endeavors to respond to the problems caused by climate change and are leading to higher temperatures inside homes, which can cause skin conditions (such as eczema), lethargy, and poor concentration; disturbed sleep and fatigue are also rising. The energy performance of buildings is influenced by interactions and associations of numerous different variables, such as the envelope specifications as well as the design, technologies, apparatuses, and occupant behaviours. This paper introduces simple and sust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…The final screening process yielded 41 relevant studies in the AMM countries, with 32 studies found in Mashreq countries and 9 in Maghreb countries, as shown in Figure 7. In the Mashreq countries, there were 18 studies in Jordan [64,65,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84], 9 in Egypt [85][86][87][88][89][90][91][92][93][94], 2 in Palestine [95,96], 2 in Iraq [97,98], 1 in Lebanon [99], and no study was presented for Syria. In the Maghreb countries, there were 5 studies in Algeria [100][101][102][103][104], 3 in Morocco [105][106][107], 1 in Tunisia [67], and no study was presented for Libya.…”
Section: Resultsmentioning
confidence: 99%
“…The final screening process yielded 41 relevant studies in the AMM countries, with 32 studies found in Mashreq countries and 9 in Maghreb countries, as shown in Figure 7. In the Mashreq countries, there were 18 studies in Jordan [64,65,[69][70][71][72][73][74][75][76][77][78][79][80][81][82][83][84], 9 in Egypt [85][86][87][88][89][90][91][92][93][94], 2 in Palestine [95,96], 2 in Iraq [97,98], 1 in Lebanon [99], and no study was presented for Syria. In the Maghreb countries, there were 5 studies in Algeria [100][101][102][103][104], 3 in Morocco [105][106][107], 1 in Tunisia [67], and no study was presented for Libya.…”
Section: Resultsmentioning
confidence: 99%
“…A parameter that has significant importance is building air infiltration, as it refers to the volume of cold air that is carried from the external environment inside the building, which can lead to a significant rise in the heating load in the winter months. An airtight building can generate considerable savings in both energy and cost [41,42]. Based on ASHRAE codes, a value of 0.35 air changes per hour was adopted, using the updated version of the DesignBuilder software (DesignBuilder Software Ltd.: Gloucs, UK) [43].…”
Section: Methodsmentioning
confidence: 99%
“…A research paper entitled “The Water-Energy-Food Nexus and Process Systems Engineering: A New Focus” stated that 1.2 billion people globally do not have clean drinking water (Garcia & You, 2016). Climate change, socio-economic rise, dependency on foreign resources, and political conflicts all have an impact on the water-food link in the MENA region (McDonnell, 2014; Muhaidat et al, 2021). Therefore, it is necessary to study the relationship between all sectors and understand the factors that affect water-energy-food sectors to ensure a sustainable life.…”
Section: Detailed Account Of the Problemsmentioning
confidence: 99%